Occurrence of twig gall insect in aonla grown under horti-pasture system - Singh, H.V.; Kumar, Sunil; Shukla, A.K. (Indian Journal of Agroforestry, 2020)
The study was carried out on the occurrence of twig gall Betousa stylophora Swinhoe pest of aonla grown under pasture production system with different soil moisture conservation techniques for two years 2010-11. Small galls were seen just start of mansoon on tips of newly grown up branches. Different soil water conservation techniques had non-significant effect on percent incidence. However, percent of infected twig per plant was significantly varied with treatment. Maximum infected twig (73.07) per cent were recorded with black polythene mulch treatment and lowest (59.47) with staggered trench (four side). Size of galls was also varied with treatment. Maximum gall length 2.46 ± 0.54 cm with width of 1.02 ± 0.24 cm was recorded in sole aonla, while minimum gall size (length 1.88 ± 0.54 and width 0.64 ± 0.15). In staggered trench (four sides) treatment. Catterpillar length and girth was 1.09 X 0.028 (cm).